Chromothripsis in hematologic malignancies - Lagunas-Rangel, Francisco Alejandro (Experimental hematology, 2024)
•Chromothripsis occurs when chromosomes shatter and reassemble randomly.•Chromothripsis can activate oncogenes, form fusion genes, or cause loss of tumor suppressors.•Chromothripsis occurs in several hematologic malignancies and is associated with loss of TP53 in these malignancies.•Chromothripsis in hematologic malignancies is often correlated with poor prognosis. Chromotrypsis, a phenomenon resulting from catastrophic mitotic errors and genomic instability, is defined by the occurrence of multiple DNA double-strand breaks in one or more chromosomes, subsequently subject to error-prone repair mechanisms. This unique process results in extensive rearrangements in the affected chromosomes, leading to loss of tumor suppressor function, the creation of fusion genes, and/or activation of oncogenes. The importance of chromothripsis in cancer, especially in the field of hematologic disorders, underscores the intricate interplay between genomic instability and the genesis of alterations that contribute to cancer. This accentuates the critical need to unravel these complex processes for the targeted development of specific therapeutic interventions. This review delves into the analysis of chromothripsis cases in various hematologic diseases, such as leukemia, lymphoma, and myeloma, with the aim of unveiling its profound impact on patient prognosis. Furthermore, the study explores the intricate molecular mechanisms underlying chromothripsis and investigates its consequences.